2006
DOI: 10.1083/jcb.200510002
|View full text |Cite
|
Sign up to set email alerts
|

AP-2α: a regulator of EGF receptor signaling and proliferation in skin epidermis

Abstract: AP-2 transcription factors have been implicated in epidermal biology, but their functional significance has remained elusive. Using conditional knockout technology, we show that AP-2α is essential for governing the balance between growth and differentiation in epidermis. In vivo, epidermis lacking AP-2α exhibits elevated expression of the epidermal growth factor receptor (EGFR) in the differentiating layers, resulting in hyperproliferation when the receptors are activated. Chromatin immunoprecipitation and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 56 publications
6
83
0
Order By: Relevance
“…ERK activation is necessary for induction of the binding activities of AP-2 in T cells (53). Also, increased ERK signal has been reported in the absence of AP-2␣ in mouse epidermis (54). In addition, we found that blockade of AP-2 by AP-2 antisense approaches had no effect on ERK activ- for an additional 24 h and then subjecting them to Western blot analysis for COX-2, AP-2␣, and actin protein levels.…”
Section: Discussionmentioning
confidence: 60%
“…ERK activation is necessary for induction of the binding activities of AP-2 in T cells (53). Also, increased ERK signal has been reported in the absence of AP-2␣ in mouse epidermis (54). In addition, we found that blockade of AP-2 by AP-2 antisense approaches had no effect on ERK activ- for an additional 24 h and then subjecting them to Western blot analysis for COX-2, AP-2␣, and actin protein levels.…”
Section: Discussionmentioning
confidence: 60%
“…The consequences of epidermal ablation of Lrig1 (26), Mig-6 (37), or the transcription factor AP2␣ (38) are all consistent with proliferation of the interfollicular SC compartment in response to EGFR ligand stimulation. Expression of Lrig1 ensures that SC are less responsive to growth-factor stimulation than their more differentiated progeny.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is interesting that the Notch pathway is linked to early follicle development (Favier et al, 2000) and that EGFR has been recently identified as a key negative regulator of notch1 gene expression in primary human keratinocytes (Kolev et al, 2008). It is also noteworthy that AP2α , which is a negative regulator of the EGF receptor (Wang et al, 2006), also becomes strongly expressed in the emerging HF placode (Panteleyev et al, 2003). Guo et al (Guo et al, 1993) suggest that 'elevated growth response might block the mesenchymal-epithelial signalling necessary for HF morphogenesis'.…”
Section: Research Articlementioning
confidence: 99%